The Role of Financial Sectors in the Financial System - Kuldashev Farid G‘ulom o‘g‘li (Genius Journals, 2023)
This article covers the structure of the financial sector and the financial sector, and gives a short scientific definition of it. The priority directions of the strategy for the reforms and the improvement of the state financial system have been reflected.
Keywords: finance; financial system; money; capital flows